2015
DOI: 10.1186/s12889-015-2113-7
|View full text |Cite
|
Sign up to set email alerts
|

Individual and collective empowerment and associated factors among Brazilian adults: a cross-sectional study

Abstract: BackgroundThe empowerment embedded in the health area is defined as a process that can facilitate control over the determinants of health of individuals and population as a way to improve health. The aim of this study was to verify the association between individual and collective empowerment with sociodemographic conditions, lifestyle, health conditions and quality of life.MethodA cross-sectional analytical study was conducted with 1150 individuals (aged 35 to 44 years). The empowerment was determined by ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Prior studies have shown that both self-efficacy and perceived collective efficacy may be related, and that both are associated with greater psychological well-being, self-esteem, life satisfaction, better stress management (Bandura, 1997;Devonport and Lane, 2006;Siu et al, 2007;Viel-Ruma et al, 2010;Çalik et al, 2012;Roos et al, 2013) and intense positive emotions (Zumeta et al, 2020). In turn, the study by Soares et al (2015) showed that individual empowerment was also related to collective empowerment, and that both of them were associated with higher quality of life and better stress management. However, while individual empowerment was only associated with the psychological aspect of quality of life (e.g., selfesteem, body image and physical appearance, feelings), collective empowerment was associated with all aspects of quality of life, both in psychological, as well as physical, social and environment terms.…”
Section: Relation Of Perceived Collective Efficacy Empowerment and Smentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have shown that both self-efficacy and perceived collective efficacy may be related, and that both are associated with greater psychological well-being, self-esteem, life satisfaction, better stress management (Bandura, 1997;Devonport and Lane, 2006;Siu et al, 2007;Viel-Ruma et al, 2010;Çalik et al, 2012;Roos et al, 2013) and intense positive emotions (Zumeta et al, 2020). In turn, the study by Soares et al (2015) showed that individual empowerment was also related to collective empowerment, and that both of them were associated with higher quality of life and better stress management. However, while individual empowerment was only associated with the psychological aspect of quality of life (e.g., selfesteem, body image and physical appearance, feelings), collective empowerment was associated with all aspects of quality of life, both in psychological, as well as physical, social and environment terms.…”
Section: Relation Of Perceived Collective Efficacy Empowerment and Smentioning
confidence: 99%
“…Indeed, some studies (e.g., Molix and Bettencourt, 2010;Lardier et al, 2018) have shown that synergy or interaction between ethnic identity and psychological or individual empowerment can contribute to both well-being and to community participation. Notwithstanding, there are other collective factors, such as collective psychological empowerment (CPE) (Drury and Reicher, 2009) that may contribute to well-being and community participation, but that have been less investigated (Staples, 1990;Soares et al, 2015). However, neglecting the role that this sort of social variable plays in the study of well-being may lead to lower awareness of its function and, therefore, lower capacity to develop individuals and societies with greater degrees of well-being.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with the findings by Song et al [6] among urban community residents in an industrial city located in the northeast of China. Smoking and drinking has been consistently accepted as risk factors for many chronic diseases but are rarely correlated with HRQoL [27,28]. However, bearing in mind the adverse effects of these behaviors on health and the significant correlation of bad health and poor HRQoL, smoking cessation and alcohol abstinence should continually be advocated as part of public health education.…”
Section: Discussionmentioning
confidence: 99%
“…Health promotion is seen as the main strategy for the reduction of morbidity and mortality, reinforcing actions on people's LS, since many diseases (e.g., hypertension, diabetes, cancer) are consequences of harmful behaviors, such as stress, inadequate feeding, and consumption of psychoactive substances 3 , and a significant percentage of non-communicable diseases could thus be avoided 4 . Nevertheless, LS has no particular definition, it is related to habits, and it can be influenced by or developed during daily work or study activities 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Having religious beliefs and a healthy behavior has been shown to be an individual empowerment factor 3 . Although this was not within the scope of our study, our findings are in agreement with other authors, since being a religious person interferes positively in the FANATASTIC lifestyle of university students (p <0.001).…”
mentioning
confidence: 99%